Scaling up critical finance for sustainable food systems through blended finance - Apampa, Andrew; Clubb, Chris; Cosgrove, Bethany Emma; Gambarelli, Gretel; Loth, Hans; Newman, Richard; Rodríguez Osuna, Vanesa; Oudelaar, Joke; Tasse, Angele (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
Sustainable agriculture is systemically underfinanced in developing countries – disproportionately, relative to other sectors – despite its critical contribution to many SDGs. This paper provides a pathway for scaling investment for food system transformation through blended finance by mobilizing commercial banks, non-bank financial institutions and their clients. The development finance community needs to collaborate with private financial institutions and investors to leverage limited public funding and increase investment. Investment in sustainable agriculture in developing countries is risky and therefore beyond the investment